Membuat Media Pembelajaran Menyenagkan Menggunakan Google Classroom Di SMN 1 Kayangan Lombok Utara - Wahab, Abdul (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The program "Creating Fun Learning Media using Google Classroom at SMPN 1 Kayangan, North Lombok" aims to improve the effectiveness of learning by utilizing modern technology. Involving teachers and students in utilizing Google Classroom as an interactive learning platform, this program focuses on creating fun learning media, integrating technology and creativity in the teaching and learning process. By this approach, it is expected to stimulate students' interest in learning, increase participation, and strengthen the effectiveness of education at SMPN 1 Kayangan, North Lombok.